The witchstone - Neff, Henry H. (Blackstone Publishing, 2024)
"Meet Laszlo, eight-hundred-year-old demon and Hell's least productive Curse Keeper. From his office beneath Midtown, he oversees the Drakeford Curse, which involves a pathetic family upstate and a mysterious black monolith. It's a sexy enough assignment--colonial origins, mutating victims, et cetera--but Laszlo has no interest in maximizing the curse's potential; he'd rather sunbathe in Ibiza, quaff martinis, and hustle the hustlers on Manhattan's subway. Unfortunately, his division has new management, and Laszlo's ratings are so abysmal that he's given six days to shape up or he'll be melted down and returned to the Primordial Ooze. Meet Maggie Drakeford, nineteen-year-old Curse Bearer. All she's ever known is the dreary corner of the Catskills where the Drakeford Curse has devoured her father's humanity and is rapidly laying claim to her own. The future looks hopeless, until Laszlo appears at the Drakeford farmhouse one October night and informs them that they have six days--and six days only--to break the spell before it becomes permanent. Can Maggie trust the glib and handsome Laszlo? Of course not. But she also can't pass up an opportunity to save her family, even if it means having a demon as a guide ... Thus begins a breakneck international adventure that takes our unlikely duo from a hot dog stand in Central Park to the mountains of Liechtenstein, a five-star hotel in Zurich, and even the time-traveling vault of a demonic crime boss. As the clock ticks down, tough-as-nails Maggie and conniving Laszlo will uncover a secret so profound that what began as a farcical quest to break a curse will eventually threaten the very Lords of Hell." - (dust jacket)